The Effect of Credit Risk, Liquidity Risk and Operational Risk to Profitability in Conventional Banks Listed on Indonesia Stock Exchange Period 2019-2021 - Endang Sri Apriani; Silvie Eka Putri; Ramli Ramli (MEC-J (Management and Economics Journal), 2023)
This study has the aim of knowing the Effects of Credit Risk, Liquidity Risk and Operational Risk on Profitability at Conventional Banks listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The data source used is financial data in each bank's financial statements and the website www.idx.co.id. the data has been sorted based on the criteria and the research population is Conventional Commercial Banks, totaling 43 banks. The analytical model used is multiple linear regression analysis with simultaneous (F test) and partial (T test) tests using IBM SPSS Statistics 25. The results of this study can be concluded that the results of the hypothesis test concluded that Credit Risk, Liquidity Risk and Operational Risk have a simultaneous effect on Profitability. The results of the partial test concluded that Credit Risk, Liquidity Risk and Operational Risk have an effect on Profitability.